Issues and challenges toward a sustainable dam management system in Selangor, Malaysia / Norlida Ismail - Norlida, Ismail (2017)
The challenges in Water Resources Development are to meet the demand of society, agriculture, industry and energy use. Dams are built to provide for the increase in societal needs for water resources. Whenever the weather is hot, the water level of the dam becames a hot topic discussed in the media. This is due to water disruptions or leakage in the cycle of water resources in the state. This leakage occurs because development causes two threats to watersheds, in either the river or the dam. The first threat is in the reduction of the size of the catchment area and at the same time there are also increases in the demand and use of water resources. Due to development these threats make water resources become scarce. The need for water resources becomes more chronic in the event of hot weather. These two factors make the dam an important entity and source of water supply in Selangor, since all Selangor rivers are exposed to various threats of pollution and development. However the rapid development of the State is a major challenge in the management of existing dams. The existing dam management focuses on the management structure of the dam only. This study provide a better understand of the role of dams in water resources development planning in Malaysia and what would constitute a sustainable dam management system. In order to realize these aims the study examines the issues and challenges affecting dam management in the state of Selangor as it is the most rapidly developing state in Malaysia where the demand for water resources is at a very critical cross road. This research examined the main characteristics of dams, to assessed the issues in the dam basin, examined the existing dam management system, evaluated the dam management effectiveness and proposed a sustainable dam management system for Selangor. The research involved a site visit, interviews, review of documents and official writings and a revised map of the study area. The analysis carried out in this study is the map analysis area, analysis of the role and functions, document analysis and SWOC analysis. Major issues in Selangor dam management are related to human activities and the impact from urban sprawl surrounding the Kuala Lumpur and Selangor area. The urbanization in Selangor started approaching the dam basin area. Dam basin are also vulnerable to land use conflict, and other threats such as illegal dumping, angler, land clearing, and other’s. The challenges in existing dam management system in Selangor involves the weakness in enforcement, the conflicting laws and regulations in land use control, no integration between related agencies, budget allocation issues, lack of expertise in dam management systems, lack of laws, regulation, guidelines, manual, strategic plan, and the lack of public awareness. Towards a sustainable dam management system, Selangor needs to take action with a special act for the security of dams, improvement and enforcement of guidelines, prepare a strategic plan, implement land use control, encourage collaboration between agencies and to increase public awareness about the dam basin and water resources conservation.